Fortalecimiento a la identidad cultural y natural para el desarrollo turístico del Cantón Olmedo, provincia de Loja. - Durazno Cumbicus, Edwin Javier (2024)
The present degree project titled “Strengthening Cultural and Natural Identity for the Tourism Development of Olmedo Canton, Loja Province,” aims to strengthen the cultural and natural identity for the tourism development of Olmedo Canton, Loja Province. To develop the research work, two specific objectives were proposed: the first was to analyze the current tourism situation of the canton under study, where the Ricaurte Local Diagnostic Matrix (2009) was applied to gather information on the tourism component of Olmedo Canton. Subsequently, information on tourist attractions was collected using the Tourist Attraction Survey Form proposed by Mintur. Next, interview and survey techniques were used as tools to collect data from a determined number of people, with the aim of gaining a deeper understanding of the tourism reality of the territory under study. Then, a SWOT matrix was developed, highlighting the positive and negative characteristics of the canton, followed by a cross SWOT analysis from which strategies were derived for the proposal's development. The second objective was to develop a proposal for cultural and natural identity that would allow the tourism development of Olmedo Canton, which involved designing a tourism identifier and, as a complement, developing strategies for its positioning, with an emphasis on using technological tools to secure a position in the tourism market. Analyzing the results, it was determined that Olmedo Canton holds a tourism and cultural potential that, according to the residents, needs to be positioned. Thus, a tourism product was identified based on the obtained data. Finally, some conclusions were drawn, establishing that Olmedo Canton has limited tourism infrastructure but boasts a wide variety of tourist attractions, culture, traditions, and exquisite cuisine. Additionally, the population warmly welcomed the development of an identifier that represents their canton both touristically and culturally. Consequently, the recommendations are directed to the GAD and the Tourism Unit to coordinate their work, improve tourism infrastructure, use technology as a rising tool to position the canton locally, provincially, and nationally, train the population, and encourage the tourism development of the territory.